Education, State Ideologies, and International Conflict: A Sociological Framework for Peacebuilding and Social Cohesion - Isufaj, Mentor (European Journal of Social Science Education and Research, 2025)
This article examines how state ideologies and the conflictual structure of the international system interact with social processes that shape war and peace, and it explains why education is a central mechanism for mitigating international conflict. Using a qualitative, theory-driven synthesis of international relations, political sociology, and sociology of education, the paper identifies key pathways through which conflict is produced and reproduced: strategic insecurity under anarchy, ideological polarization, nationalism, and identity-based mobilization especially during political transitions. The analysis shows that schooling can amplify these dynamics through selective historical memory, exclusionary civic narratives, and segregated learning environments, but it can also reduce conflict risks by strengthening social cohesion, democratic competencies, and critical media literacy. The article concludes that conflict-sensitive education and peace-oriented social science curricula are not “add-ons” but institutional strategies that can reshape intergroup relations and increase resilience to ideological manipulation. The study contributes to social science education by linking macro-level conflict theories to concrete curricular and pedagogical interventions.